Combatting the “great discontent”: the impact of employability culture and leadership empowerment on career growth, loyalty and satisfaction - LaGree, Danielle; Olsen, Katie; Tefertiller, Alec; Vasquez, Rosalynn (My University, 2023)
Purpose Motivated by the organizational challenge coined the great discontent, employees are dissatisfied with their jobs, see minimal opportunities for growth and are actively searching for new roles. This research aims to take a novel approach to internal communication strategy by introducing employability culture and leadership empowerment as mechanisms for supporting employees' career growth and additional positive workplace outcomes. Design/methodology/approach An online survey was designed and administered in the United States. The final sample size includes 425 full-time employees working in a variety of roles, industries and work arrangements. Findings Findings point to the inherent need for revised internal communication strategy that goes beyond managing and disseminating information. Organizations must develop cultures and their leaders in ways that empower employees and help them understand the meaning of their work. Employability culture, or an organization's support for developing employees' adaptive skills as work roles change, positively predicted employees' perceptions of their career growth opportunities at their current place of employment, employee loyalty and engagement, and job satisfaction. Leadership empowerment behaviors also positively predicted all previously listed workplace variables. These perceptions as influenced by work arrangement (onsite, hybrid, fully remote) and younger versus older generations were also analyzed. Originality/value Research findings offer new strategies for internal communications. Internal communication teams can partner alongside executive leadership to develop a culture that helps employees envision how their skills and expertise translates to different areas of the organization, empowering them to find meaning in their work, and be driven to support organizational growth.
Keywords: Internal communication; The great discontent; Leadership empowerment; Employability culture; Career Growth; Employee Loyalty